How Effective İs The Nigerian Senior School Agricultural Science Curriculum? A Survey Of Evidence From Content Development To Product - Samson Akinwande Akanmu; Adejare Solomon Olorundare; Johnson Uphai (European Scientific Journal, ESJ, 2016)
Agricultural science, a vocational subject in Nigerian senior schools is yet to meet its objectives due to various challenges. Consequently, the performance of students in the subject is relatively poor. This study examined the effectiveness of the Nigerian senior school agricultural science curriculum. 255 teachers and 255 students were engaged for the study. Teachers’ Curriculum Evaluation Instrument (TCEI) and Agricultural Achievement Test (AAT) were used for data collection. Data were analysed using descriptive statistics. Findings from the study show that 86% of the teachers perceived the agricultural science curriculum content were suitable for students’ performance, the instructional facilities for agricultural science teaching in schools are not adequately available and agricultural science curriculum implementation was confronted with several challenges. Student performance in agricultural science was poor as about 51% had credit pass in the administered test and 49% failed the test. Using the CIPP frame work, this study concluded that the context (content) is suitable, input (instructional facilities) is deficient, process (implementation) is highly deficient and consequently, the (product) student performance in agricultural science is poor. It is recommended that among others that concerned stakeholders should adequately provide instructional facilities, ensure their adequacy and also supervise their judicious utilization.